Pengelolaan Pembelajaran Bahasa Indonesia Berbasis Farmasi di SMK Muhammadiyah 4 Surakarta - Rosyidi, Ali; , Dr. Suyatmini, M.Si; , Dr. Sabar Narimo, M.M., M.Pd (2015)
ABSTRACT Ali Rosyidi, Indonesian Learning Management Based Pharmaceutical SMK Muhammadiyah 4 Surakarta. Thesis, Master of Education Administration Graduate Program, University of Muhammadiyah Surakarta. This study aimed to describe about 1). Indonesian learning plan based pharmaceuticals. 2). Indonesian implementation of learning-based pharmaceuticals. 3). Evaluation of pharmaceutical-based learning Indonesian. The research method using descriptive qualitative. The study design with a case study. The object of research is the Principal, Vice Principal, Teacher, participants Didik.Teknik data collection through observation, interview and documentation study. Analysis and processing of data is done by: 1) the reduction of the data; 2) the presentation of data; and 3) take the conclusion or verification. In order to obtain valid data, triangulation data and source, which means that the same data revealed from various sources. The results showed that: 1) the planning activity-based learning Indonesian pharmaceutical SMK Muhammadiyah 4 Surakarta basically been carried out properly. This can be seen in the administration of learning made by teachers Indonesian, 2) Implementation of the learning Indonesian-based pharmaceutical SMK Muhammadiyah 4 Surakarta balancing theory and practice, this activity leads to the pharmaceutical field as the hallmark of a school. This can be seen with the habituation and the routine use of language that is done every day, and 3) pharmaceutical-based learning Indonesian in SMK Muhammadiyah 4 Surakarta basically already implemented sustainability. This is evident in the implementation of the assessment carried out in stages, starting from the daily tests, daily tests programmed, mid term, and the replay end of the semester. Keywords: management, learning, Indonesian, pharmacy